2020
DOI: 10.1021/acsami.9b21890
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and Giant Terahertz Modulation Based on Ultra-Strain-Sensitive Conductive Polymer Composites

Abstract: Dynamic tuning of terahertz (THz) wave has a great potential application as smart THz devices, such as switches, modulators, sensors, and so on. However, the realization of flexible THz modulation with high efficiency is rarely observed, which is nearly absent from the booming development and demands on flexible electronics. Here, we report a flexible THz modulation based on conductive polymer composites composed of thermoplastic polyurethane (TPU) and conductive particles (Ni). By designing the additive conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…On the basis of the experimental results, it is inferred that there are three factors for changing the THz reflection wave from the SiO 2 /MXene/air interface, which are the layer numbers of MXene films, the concentrations of MXene dispersions, and the incident angle of THz pulse. Generally, THz reflection modulation is usually based on external conditions such as temperature, mechanical force, laser, electric field, and so on. ,,, But in this work, THz reflection can be modulated by changing substrates coated with different MXene films, and this can be achieved by simply having a specimen holder that can hold multiple samples and can be rotated or moved. Furthermore, our functional MXene films can be used for THz antireflection or reflection-enhancing coatings by stacking the appropriate layer numbers of films on the substrate or changing the concentrations of the MXene dispersions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the experimental results, it is inferred that there are three factors for changing the THz reflection wave from the SiO 2 /MXene/air interface, which are the layer numbers of MXene films, the concentrations of MXene dispersions, and the incident angle of THz pulse. Generally, THz reflection modulation is usually based on external conditions such as temperature, mechanical force, laser, electric field, and so on. ,,, But in this work, THz reflection can be modulated by changing substrates coated with different MXene films, and this can be achieved by simply having a specimen holder that can hold multiple samples and can be rotated or moved. Furthermore, our functional MXene films can be used for THz antireflection or reflection-enhancing coatings by stacking the appropriate layer numbers of films on the substrate or changing the concentrations of the MXene dispersions.…”
Section: Resultsmentioning
confidence: 99%
“…Terahertz (THz) is an electromagnetic wave between the microwave and infrared region with a frequency range of 0.1–10 THz. It has significant importance in biological imaging, nondestructive detection, sensors, next-generation communications, and so on. The development of highly efficient THz modulation devices is fundamental for these applications. , Although many studies focused on THz modulators including 2D materials, metal oxides, , semiconductors, metamaterials, and photonic crystals, achieving broadband, angle-agile, convenient, and giant THz modulation remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…controlled the transmission of THz wave by preparing and stretching a composite of thermoplastic polyurethane and nickel nanoparticles. [ 43 ] These studies, together with some other work, [ 44–47 ] demonstrated the potential to mechanically modulate the EM wave in THz regime by using the flexible and stretchable metasurface. However, the current strategies to design the flexible and stretchable metasurface are heavily relied on the soft elastomers, such as PDMS and Ecoflex.…”
Section: Introductionmentioning
confidence: 99%
“…This flexible layer exhibits the resistivity change of six to seven orders under tensile strain, which can be used to control the THz transmission with a giant modulation depth as high as 96%. Starting from the structural role of metamaterials, THz radiation can be modulated flexibly using the properties of materials [28]. Therefore, flexible material modulators with simple structures and obvious effects are desirable.…”
Section: Introductionmentioning
confidence: 99%